Communication and ritual on jaranan pogogan: The semiotics of performing arts - Laksono, Yunanto Tri (Faculty of Communications Science, Dr. Soetomo University, 2021)
The main objective of this research was to study culture and arts in the form of performing arts, which have a significant role in the preservation of tradition through the perception of communication semiotics. The suguh ritual is a presentation that is carried out before the jaranan pogogan traditional performance art activity in Nganjuk Regency. The suguh ritual is expected to represent language indirectly through the semiotics of communication during its implementation. In addition, the preservation of traditional performing arts through the perception of this ritual can provide the right image to maintain the preservation of traditional arts in the Nganjuk Regency. This ritual of regeneration is still occurring to this day. This research was a qualitative descriptive study. The literacy process used to determine information results were obtained from informants who distributed data in Nganjuk Regency. Researchers also conducted interviews, observed and collected data in the field. This research is expected to preserve the jaranan pogogan’s role in the suguh ritual and serve as non-degraded cultural manifestations in technological developments 4.0.